The Sunset of Social Democracy in East-Central Europe: Case Study of Hungary - Gudžinskas, Liutauras (Politologija, 2020)
The article analyzes the reasons of the long-term decay of the Hungarian Socialist Party (MSZP) since 2010. The party ruled the country between 1994–1998 and 2002–2010 and was one of the strongest and most institutionalized political forces not only in Hungary but in the whole East-Central Europe. However, during the parliamentary elections in 2010, it suffered a crushing defeat by their main political opponents – “Fidesz,” led by V. Orbán. The organizational development of these two parties is compared. Collected evidence reveal the significance of centralized party rule and efforts to organize civil society in shaping the intra-competition of the main Hungarian political parties.